-3(y-4y)+6=-4(2y-y)+4+12y

Simple and best practice solution for -3(y-4y)+6=-4(2y-y)+4+12y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(y-4y)+6=-4(2y-y)+4+12y equation:


Simplifying
-3(y + -4y) + 6 = -4(2y + -1y) + 4 + 12y

Combine like terms: y + -4y = -3y
-3(-3y) + 6 = -4(2y + -1y) + 4 + 12y

Remove parenthesis around (-3y)
-3 * -3y + 6 = -4(2y + -1y) + 4 + 12y

Multiply -3 * -3
9y + 6 = -4(2y + -1y) + 4 + 12y

Reorder the terms:
6 + 9y = -4(2y + -1y) + 4 + 12y

Combine like terms: 2y + -1y = 1y
6 + 9y = -4(1y) + 4 + 12y

Remove parenthesis around (1y)
6 + 9y = -4 * 1y + 4 + 12y

Multiply -4 * 1
6 + 9y = -4y + 4 + 12y

Reorder the terms:
6 + 9y = 4 + -4y + 12y

Combine like terms: -4y + 12y = 8y
6 + 9y = 4 + 8y

Solving
6 + 9y = 4 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
6 + 9y + -8y = 4 + 8y + -8y

Combine like terms: 9y + -8y = 1y
6 + 1y = 4 + 8y + -8y

Combine like terms: 8y + -8y = 0
6 + 1y = 4 + 0
6 + 1y = 4

Add '-6' to each side of the equation.
6 + -6 + 1y = 4 + -6

Combine like terms: 6 + -6 = 0
0 + 1y = 4 + -6
1y = 4 + -6

Combine like terms: 4 + -6 = -2
1y = -2

Divide each side by '1'.
y = -2

Simplifying
y = -2

See similar equations:

| 4x^2+24x^2+36x^2=4x^2+16x+16 | | 35x^7+25x^5+15x^3= | | 120/55=45.6/a | | -10-8x=7+3(x+1) | | -2=3y-18-55y | | 4x^4-75xy^3=0 | | 4x^2+25x^5+26x^4=4x^2+16x+16 | | x^2+6x-4= | | 30y^3+84y+120y^2= | | 2y^2-13y+20=0 | | 4(x)-8(x+1)=8 | | 4x-14=6(x-3) | | 13-2/9x=9 | | (x^3+x^2+2x-4)/(x-1) | | -15+x=x+20 | | x^2+24x+36=36x+81 | | 5(a-7)+10=3(a-5) | | -10x-19=19+-8x | | (1/5)-(1/4) | | 31+x=3(5+3x) | | x(x+8)=308 | | 6(5r+3)=-15-3r | | 800+16y=720+21y | | (2-3x)+(3-4x)= | | B-5+2b=26 | | 110-x+4x=180 | | 4x^6+24x^5+36x^4=4x^2+16x+16 | | 0.7x-0.7(6-x)=4.9 | | b^2-5/3b=0 | | 8-3z=(-2+6)+6(3z+4) | | 4x+16z=y | | a+b+b+b+80+99=100 |

Equations solver categories